2014
DOI: 10.1016/j.pss.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

In situ biological resources: Soluble nutrients and electrolytes in carbonaceous asteroids/meteorites. Implications for astroecology and human space populations

Abstract: Ecosystems in space will need in-situ bioavailable nutrients. The measured nutrients in meteorites allow experiment-based estimates of nutrients in asteroids, and of the biomass and populations that can be derived from these in situ bioresources. In this respect, we found that carbonaceous chondrite meteorites can support microorganisms and plant cultures, suggesting that similar asteroid materials are also biologically fertile. The sustainable biomass and populations are determined by the available resource m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In these studies, meteorite models of asteroid materials showed that bacteria, algae and plants can grow on asteroid/meteorite organics and electrolytes, with fertilities similar to productive agricultural soils [4,8,9,26,[57][58][59][60][61]. Based on the measured soluble nutrient contents, asteroid resources can yield a biomass of 10 18 kg in the Solar System.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, meteorite models of asteroid materials showed that bacteria, algae and plants can grow on asteroid/meteorite organics and electrolytes, with fertilities similar to productive agricultural soils [4,8,9,26,[57][58][59][60][61]. Based on the measured soluble nutrient contents, asteroid resources can yield a biomass of 10 18 kg in the Solar System.…”
Section: Discussionmentioning
confidence: 99%
“…The resources and populations in various stages of space settlements, up to cities of millions, were examined recently [26].…”
Section: The Human Rolementioning
confidence: 99%
“…Of particular interest are those that have hydrated minerals on their surfaces (Feierberg et al 1981;Milliken & Mustard 2007;Alexander et al 2012). With the recent data received from the Hayabusa 2, OSIRIS-REx missions, and their meteorite analogs, the C-type asteroids are of interest for crewed missions, as they have been postulated to contain hydrated minerals, rare-earth elements (albeit in low abundance), and bioavailable nutrients that could sustain sizable populations, particularly in space agriculture (Jones et al 1990;Gaffey et al 1993;Merényi et al 1997;Jewitt et al 2007;Mautner 2014;Martínez-Jiménez et al 2017). Both the CI and CM subclasses of the carbonaceous chondrite meteorites are targets for use in space agriculture owing to their relatively high carbon content (1.5%-6%) and degree of aqueous alteration (Wasson & Kallemeyn 1988;Cruikshank 1997;Scott & Krot 2003).…”
Section: Introductionmentioning
confidence: 99%